2014
DOI: 10.1364/oe.22.011090
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-based waveguide polariser: From thin film to quasi-bulk

Abstract: We have demonstrated a broadband waveguide polariser with high extinction ratio on a polymer optical waveguide coated with graphene oxide via the drop-casting method. The highest extinction ratio of nearly 40 dB is measured at 1590 nm, with a variation of 4.5 dB across a wavelength range from 1530 nm to 1630 nm, a ratio that is (to our knowledge) the highest reported for graphene-based waveguide polarisers to date. This result is achieved with a graphene oxide coating length along the propagation direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…It was found that the TE-polarized light is suppressed by the GO-coated waveguide to more than −20 dB with reference to TM-polarized light. Suppression of the TE-mode is due to absorption of electric field by the GO layers, which was reported in [ 25 ].…”
Section: Device Fabrication and Experimentsmentioning
confidence: 76%
“…It was found that the TE-polarized light is suppressed by the GO-coated waveguide to more than −20 dB with reference to TM-polarized light. Suppression of the TE-mode is due to absorption of electric field by the GO layers, which was reported in [ 25 ].…”
Section: Device Fabrication and Experimentsmentioning
confidence: 76%
“…[87][88][89] Although label-free optical biosensing platforms have been reported to be enhanced by using structural properties of GO, as far as we are concerned, the elucidation of the optical/photonic properties or phenomena underlying such improvements have been scarcely elaborated until now, which can be subject of in-depth investigation. [94][95][96] Recently, Chung et al, reported the SPR enhancement at pristine graphene/metal (Au) interface. [90] Optical fibers are a particular example of optical waveguides.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
“…In Ref. [15], a broadband GO-polymer waveguide polarizer with a high PDL of ~ 40 dB was demonstrated, where the GO films were introduced onto an SU8 polymer waveguide using drop-casting methods. The GO film thickness for each drop-casting step was ~ 0.5 µm and the drop coating diameter was ~1.3 mm, neither being ideal for achieving precise control of the placement, thickness, and length of the GO films.…”
Section: Introductionmentioning
confidence: 99%